Analisis Kesalahan Fonologi Dalam Kegiatan Bimbingan Al-Qur’an Intensif Di Kelas X Smk Muhammadiyah 4 Yogyakarta - Suharsono; Syaikha Dziyaulhaq Zein; Nida Farhani Mubarokah (Program Studi Pendidikan Bahasa Arab Universitas Nahdlatul Ulama Purwokerto, 2023)
Analysis of Phonological Errors in Intensive Qur'an Reading Guidance Activities of Class X SMK Muhammadiyah 4 Yogyakarta. This study aims to explain the various forms of phonological errors, the inhibiting factors in the intensive Qur'an reading guidance activities of class x students of SMK Muhammadiyah 4 Yogyakarta. This research uses descriptive qualitative research through observation, interview and documentation. The research problem is that there are inaccuracies in the pronunciation of language sounds such as high and low tones, intonation of sounds when students deposit reading the Qur'an in intensive Qur'anic Guidance activities which are held every Wednesday with a duration of approximately 45 minutes. Data in the form of pronunciation errors, reading the Qur'an. The data were collected using observation methods, recording notes and individual interviews to several learners. The results of the study prove that several prenounciation and reading errors were found in the Intensive Qur'anic Guidance activities of Class X SMK Muhammadiyah 4 Yogyakarta based on inappropriate intonation, pronunciation of letter sounds, dialectics of regional languages. The solution that should be taken by teachers in overcoming these phonological errors is to make the learning of Intensive Qur'anic Guidance fun and pay good attention and apply material that is interesting and easily captured by class X students of SMK Muhammadiyah 4 Yogyakarta.